MODERNIZATION OF MANAGEMENT SYSTEMS OF ENTERPRISES IN THE SERVICE FIELD (Development Service Industry Management, 2025)
The article is devoted to the analysis of factors and factors of modernization of service enterprises. A conceptual model of modernization of enterprises in the service sector is proposed. A list of tools for modernization of the flexible management system of the hotel business of the enterprise is provided. It is shown that the development of a modern concept of modernization of the hotel industry based on the formation of a flexible management system is able to ensure the dynamic development of enterprises in an unstable external and internal environment. It has been proven that the development of a modern concept of hotel modernization based on the formation of a flexible management system is able to ensure the dynamic development of enterprises in an unstable external and internal environment. The peculiarities of the service sector, which also imply the specifics of the use of modernization processes in it, are substantiated. The peculiarities of the service sector are such that flexible management, aimed at ensuring the strategic stability of a service sector enterprise, should involve the formation of modernization tools: business communications, the introduction of flexible budgeting and competitiveness monitoring. It was found that the advantages of the modernization path of hotel business development are significantly reduced outside the context of the formation of a flexible management system. The modernization of the management system is characterized, which should be carried out within the framework of the concept of strategic sustainability, take into account the entrepreneurial nature of the hotel business and ensure the development of the adaptive nature of individual business processes. In the conditions of permanent changes in the state of the modern service market and fierce competition among hotel service enterprises, methods have been developed for assessing the effectiveness of the flexible management system for their sustainability, which is an important direction for the modernization of the management apparatus. A set of assessments of the effectiveness of the flexible management system for the sustainability of service enterprises has been developed, which includes the calculation of financial stability indicators, assessment of communication efficiency, and competitiveness.
Keywords: modernization; management system; enterprise; service sector; hotel business